A Novel Mutation in Lafora Disease and Update on Pathophysiology and Future Treatments. (October 2022) - Nordli, Douglas R.; Rao, Chethan K.; Delgado-Escueta, Antonio V.; Galan, Fernando
Lafora disease is a rare refractory epilepsy that results in death. This report highlights two cases of lafora disease and introduces a novel mutation in the patients. A review of the pathophysiology and future therapies is reviewed.